Coupling of crop and livestock production can reduce the agricultural GHG emission from smallholder farms - Xiangbo Xu; Yan Xu; Jing Li; Yonglong Lu; Alan Jenkins; Robert C. Ferrier; Hong Li; Nils Chr Stenseth; Dag O. Hessen; Linxiu Zhang; Chang Li; Baojing Gu; et al. (iScience, 2023)
Summary: Ensuring global food security and environmental sustainability is dependent upon the contribution of the world’s hundred million smallholder farms, but the contributions of smallholder farms to global agricultural greenhouse gas (GHG) emissions have been understudied. We developed a localized agricultural life cycle assessment (LCA) database to calculate GHG emissions and made the first extensive assessment of the smallholder farms’ GHG emission reduction potentials by coupling crop and livestock production (CCLP), a redesign of current practices toward sustainable agriculture in China. CCLP can reduce the GHG emission intensity by 17.67%, with its own feed and manure returning to the field as an essential path. Scenario analysis verified that greater GHG emission reduction (28.09%–41.32%) will be achieved by restructuring CCLP. Therefore, this mixed farming is a mode with broader benefits to provide sustainable agricultural practices for reducing GHG emissions fairly.